PVDF/TiO2/PEG Hollow Fiber Membrane for Oily Wastewater Treatment at Various Concentration of Oily Wastewater - Fithri Yatul Humairo; Chi Siang Ong; Nurul Widiastuti; Ahmad Fauzi Ismail; Shabrina Adani Putri; Juhana Jafar (IPTEK Journal of Proceedings Series, 2015)
The purpose of this research is to enhance the performance of PVDF/TiO2 membrane particularly permeate flux in the application of oily wastewater treatment by adding Polyethylene glycol (PEG). Various concentration of oily wastewater was conducted in order to investigate the influence of the concentration on the membrane performance. Results show that by adding the PEG into the PVDF/TiO2 membrane, the permeate flux of oily wastewater was increase compared to PVDF/TiO2 membrane without PEG. The permeate flux was affected by concentration of synthetic oily wastewater. Increasing the concentration of synthetic oily wastewater, decreasing the flux of oily wastewater